Needs Analysis in the Development of an Ethnoscience-Based Educative Magazine - Nadifah, Imroatun; Fikriyah, Aida; Ahied, Mochammad (Indonesian Journal of Mathematics and Natural Science Education, 2023)
This study aims to analyze the need for the development of an ethnoscience-based educative magazine on the topic of petis lorjuk Madura. The results of the scientific reconstruction can be packaged in natural science teaching materials in the form of educative magazines. This research is qualitative descriptive research, using interviews, observation, and documentation techniques. The stages of the research started with preparation, making research instruments, implementation, and completion. The results of this study are the community's indigenous knowledge about making petis lorjuk with STEAM reviews. The results of this study found reinforcement and misconceptions where there is a correlation between the ethnoscience study of petis lorjuk and natural science material. The results of the ethnoscience study that have been obtained can be used as science teaching materials contextually and can review further related misconceptions of knowledge so that learning is more meaningful and sensitive to the surrounding environment.